2022
DOI: 10.1155/2022/1024161
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cryptography Based on Multiple Exponentiation Problem of Matrices

Abstract: Because there is no multiplication of numbers in tropical algebra and the problem of solving the systems of polynomial equations in tropical algebra is NP-hard, in recent years some public key cryptography based on tropical semiring has been proposed. But most of them have some defects. This paper proposes new public key cryptosystems based on tropical matrices. The security of the cryptosystem relies on the difficulty of the problem of finding multiple exponentiations of tropical matrices given the product of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to Reference [19], we can give the definition of the ME problem of the tropical Jones matrix.…”
Section: Multiple Exponentiation Problem Of Tropical Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Reference [19], we can give the definition of the ME problem of the tropical Jones matrix.…”
Section: Multiple Exponentiation Problem Of Tropical Matricesmentioning
confidence: 99%
“…Hence, its modifications are not resistant to the generalized KU attack. In 2022, Huang and Li proposed a new key exchange protocol [19] based on the multiple exponentiation problem of matrices, using tropical algebra as a platform and the adjoint matrix of the first polynomial. The analysis results showed that the protocol can resist all known attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse matrix forms were incorporated, ranging from singular [2,3] and non-singular matrices [4] to matrices over bit strings [5]; Tribonacci matrices [6]; Hadamar matrices [7]; non-negative [8] and lattice matrices [9]. Tropical matrices are also of interest ( [10][11][12][13][14][15]). Yet, despite these developments, vulnerabilities have persisted, as evidenced by different documented attacks (see, for example, [16][17][18][19]).…”
Section: Introductionmentioning
confidence: 99%
“…Various schemes using tropical matrices have been suggested in [11][12][13][14][15][16]; yet, despite these developments, vulnerabilities have persisted, as evidenced by different documented attacks (see for example [17][18][19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%